Saltwater Intrusion Zone Mapping on Shallow Groundwater Aquifer in Selat Baru, Bengkalis Island, Indonesia - Dewandra Bagus Eka Putra; Yuniarti Yuskar; Husnul Kausarian; Wan Zuhairi Wan Yaacob; Mohamad Sapari Dwi Hadian (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
Saltwater intrusion becomes a common problem in coastal area. Northern coast of Bengkalis Island in Riau, Indonesia that contiguously to Malacca Strait is experiencing the problem particularly in Selat Baru area which considered as developing area and most of the people live close to the sea. Dug well is the main source of groundwater that had been used by the population in Selat Baru and as the increasing of land occupation, the demand of clean water is rising up followed by the number of dug well. A study of groundwater monitoring was conducted to identify the zone of saltwater intrusion. Field observation had done by measuring the water level and physical parameters of groundwater such as taste, pH, electrical conductivity (EC) and total dissolved solid (TDS) from 110 existing dug wells. Some conus feature had found from groundwater elevation map which indicated lower water level caused by excessive groundwater pumping. Generally, pH shows values from 6-8 that was still in range of water quality standard, but there are 20 wells (18%) that have pH below the water quality standard (slightly acidic water). Similar pattern had been observed from Electrical Conductivity (EC) and Total Dissolved Solid (TDS) map, higher value of EC and TDS was dominant in the northern part of study area and lower value in the south. Groundwater taste map also revealed the identical condition with EC and TDS map which dominated by brackish and saline water in the northern part. Therefore, the study area had been divided into two zones of groundwater saline water zone possibly caused by the saltwater intrusion in the northern part and freshwater zone from the center to the southern part.